Poverty Reduction without Economic Growth? Explaining Brazil's Poverty Dynamics, 1985-2004 - Ferreira, Francisco H.G.; Leite, Phillippe G.; Ravallion, Martin (2012)
Brazil's slow pace of poverty reduction between the mid-1980s and the mid-2000s reflects both low growth and a low growth elasticity of poverty reduction. Using GDP data disaggregated by state and sector for a twenty-year period, this paper finds considerable variation in the poverty-reducing effectiveness of growth--across sectors, across space, and over time. Growth in the services sector was substantially more poverty-reducing than was growth in either agriculture or industry. Growth in industry had different effects on poverty across different states and its impact varied with initial conditions related to human development and worker empowerment. But because there was so little of it, economic growth actually played a relatively small role in accounting for Brazil's poverty reduction between 1985 and 2004. The taming of hyperinflation (in 1994) and a substantial expansion in social security and social assistance transfers, in large part mandated by the 1988 Constitution, accounted for the bulk of the overall reduction in poverty.